TPX2 Enhanced the Activation of the HGF/ETS-1 Pathway and Increased the Invasion of Endocrine-Independent Prostate Carcinoma Cells - Zhou, Hongqing; Liu, Mingsheng; Shao, Tao; Xie, Pingbo; Zhu, Shaojie; Wang, Wei; Miao, Qiong; Peng, Jiaxi; Zhang, Peng (Frontiers in Oncology, 2021)
The prognosis for endocrine-independent prostate carcinoma is still poor due to its highly metastatic feature. In the present work, TPX2 (the targeting protein for Xklp2), which is known as a micro-tubulin interacted protein, was identified as a novel coactivator of ETS-1, a transcription factor that plays a central role in mediating the metastasis of human malignancies. TPX2 enhanced the transcription factor activation of ETS-1 and increased the expression of ETS-1’s downstream metastasis-related genes, such as mmp3 or mmp9, induced by HGF (hepatocyte growth factor), a typical agonist of the HGF/c-MET/ETS-1 pathway. The protein-interaction between TPX2 and ETS-1 was examined using immunoprecipitation (IP). TPX2 enhanced the accumulation of ETS-1 in the nuclear and the recruitment of its binding element (EST binding site, EBS) located in the promoter region of its downstream gene, mmp9. Moreover, TPX2 enhanced the in vitro or in vivo invasion of a typical endocrine-independent prostate carcinoma cell line, PC-3. Therefore, TPX2 enhanced the activation of the HGF/ETS-1 pathway to enhance the invasion of endocrine-independent prostate carcinoma cells and thus it would be a promising target for prostate carcinoma treatment.